The best evidence for progressive myoclonic epilepsy: A pathway to precision therapy. (October 2019) - Orsini, Alessandro; Valetto, Angelo; Bertini, Veronica; Esposito, Mariagrazia; Carli, Niccolò; Minassian, Berge A.; Bonuccelli, Alice; Peroni, Diego; Michelucci, Roberto; Striano, Pasquale
Highlights: The incidence of PMEs is growing more and more each passing day. PMEs are one of the most serious epileptic syndromes. Precision Medicine is the weapon to deal with these diseases considered incurable. Abstract: Progressive Myoclonus Epilepsies (PMEs) are a group of uncommon clinically and genetically heterogeneous disorders characterised by myoclonus, generalized epilepsy, and neurological deterioration, including dementia and ataxia. PMEs may have infancy, childhood, juvenile or adult onset, but usually present in late childhood or adolescence, at variance from epileptic encephalopathies, which start with polymorphic seizures in early infancy. Neurophysiologic recordings are suited to describe faithfully the time course of the shock-like muscle contractions which characterize myoclonus. A combination of positive and negative myoclonus is typical of PMEs. The gene defects for most PMEs (Unverricht-Lundborg disease, Lafora disease, several forms of neuronal ceroid lipofuscinoses, myoclonus epilepsy with ragged-red fibers [MERRF], and type 1 and 2 sialidoses) have been identified. PMEs are uncommon disorders, difficult to diagnose in the absence of extensive experience. Thus, aetiology is undetermined in many patients, despite the advance in molecular medicine. Treatment of PMEs remains essentially symptomaticof seizures and myoclonus, together with palliative, supportive, and rehabilitative measures. The response to therapy may initially be relatively favourable, afterwards however, seizures may become more frequent, and progressive neurologic decline occurs. The prognosis of a PME depends on the specific disease. The history of PMEs revealed that the international collaboration and sharing experience is the right way to proceed. This emerging picture and biological insights will allow us to find ways to provide the patients with meaningful treatment.